Pelaksanaan Latihan Kegel untuk Mengurangi Nyeri Luka Perineum pada Ibu Postparent Normal - Erna Kasim; Sri Nanda; Magdalena Limbong; Ekayanti Hafidah Ahmad; Andi Tenriola Fitri Kessi (Lembaga Pengembangan Kinerja Dosen, 2025)
Perineal pain is a common complaint experienced by postpartum mothers due to the normal delivery process. The intensity of pain felt is subjective and can be different from individual to individual, influenced by physical conditions and pain management approaches applied by health workers. Effective pain management is essential to support the fulfillment of the basic needs of postpartum mothers and speed up the recovery process. This study aims to determine the effect of Kegel exercises on the intensity of perineal wound pain in normal postpartum mothers at Pelamonia Class II Hospital, Makassar. The research design used was a case study with a descriptive approach, involving two respondents who experienced postpartum perineal pain. Kegel exercises were performed regularly, and pain intensity was measured before and after the intervention on the third day postpartum. The results showed that both respondents experienced a decrease in pain intensity from moderate to mild after doing Kegel exercises. These findings suggest that Kegel exercises may be one of the effective non-pharmacological methods in reducing perineal pain in normal postpartum mothers. The conclusions of this case study confirm the importance of education and the application of Kegel exercises as part of holistic postpartum care. This research is expected to be a reference for health workers in improving the quality of maternal services through a simple, safe, and useful approach.